2017
DOI: 10.1016/j.tjog.2016.12.019
|View full text |Cite
|
Sign up to set email alerts
|

The utility and effectiveness of an internal iliac artery balloon occlusion catheter in surgery for large cervical uterine fibroids

Abstract: For large cervical fibroids with limited operating space, surgery was performed under bleeding control by occlusion of the internal iliac artery with an IIABOC. This technique enables control of hemorrhage and safe operative management in gynecological surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…For a cervical myoma of the uterus and giant uterine leiomyoma that leave no intrapelvic space and prevent palpation and identification of the uterine arteries and the internal iliac arteries, surgery can be performed safely by preoperatively placing balloon catheters in the internal iliac arteries. 1,3 Thus, if this procedure is regarded as one of the feasible approaches, the procedural options for performing myomectomy will likely further increase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For a cervical myoma of the uterus and giant uterine leiomyoma that leave no intrapelvic space and prevent palpation and identification of the uterine arteries and the internal iliac arteries, surgery can be performed safely by preoperatively placing balloon catheters in the internal iliac arteries. 1,3 Thus, if this procedure is regarded as one of the feasible approaches, the procedural options for performing myomectomy will likely further increase.…”
Section: Resultsmentioning
confidence: 99%
“…Indication of this IIABOC is myomectomy for a huge uterine cervical myoma and giant uterine leiomyomas that leave no intrapelvic space and prevent palpation and identification of the uterine arteries and the internal iliac arteries. [1][2][3] Balloon catheters are inserted from each side of the groin and placed in the contralateral internal iliac arteries by the Seldinger technique. Then, the balloons are inflated to interrupt the blood flow to the uterine arteries.…”
Section: Internal Iliac Artery Balloon Occlusion (Iiaboc)mentioning
confidence: 99%
“…As shown in Tab. 1, the cervical myomectomies were performed via laparoscopic, open, and vaginal approaches, respectively, in 198 (71.48%), 41 (14.8%), and 38 (13.72%) patients in English studies [23,24,26,[33][34][35][36][37][38][39][40][41], including case report studies CR#1 -CR#5 represented in (Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…The growing number of publications on this topic demonstrated that the prevalence of CFs is underestimated and they could initiate a severe medical condition with miscellaneous symptoms and require challenging surgical treatment for fertility preservation and lifesaving management in obstetric patients [26][27][28]. Therefore many diagnostic and treatment technologies to manage CFs were described in the literature [29][30][31][32][33][34][35][36][37]. According to the recent systematic literature review, laparoscopy was the most frequently used approach in 114 (59.4%) patients among 192 identified cases of surgical and radiologic interventional treatments [37].…”
Section: Introductionmentioning
confidence: 99%
“…A single case report exists in the literature in which internal iliac arteries balloons were inserted prophylactically for a high-risk patient with HM undergoing suction curettage; however, despite a 1.1 litre blood loss, the balloons were not inflated and were removed thereafter (5). The patient however, received an oxytocin infusion following the evacuation of the uterine cavity.…”
Section: Discussionmentioning
confidence: 99%